Leveraging Nature‐based Solutions for transformation: Reconnecting people and nature. Issue 5 (3rd May 2021) - Welden, E. A.; Chausson, Alexandre; Melanidis, Marina S.
Abstract: Nature‐based Solutions (NbS) have rapidly been gaining traction across the research, policy and practice spheres, advocated as transformative actions to jointly address biodiversity loss and climate change. However, there are multiple, alternative ways to conceptualize NbS across those three spheres. To inform the NbS discourses in research, policy and practice, we critically reflect on the prevailing framing of NbS. Although the concept links environmental health to human well‐being, we argue that its current dominant framing reinforces a dichotomy between people and nature by highlighting one, external nature working for the benefit of society. For the NbS concept to support transformation, we believe it must embody a reframing of human–nature relationships towards regenerative relationships between humans and nature. To support the transformative aspirations of NbS, we propose a novel core framing of NbS making explicit the co‐dependence of people and nature, which underpins human well‐being and environmental health. We highlight how such a framing can support a transformation through influencing beliefs and normative values, and second, through the communication and application of the NbS concept in research, policy and practice. We then elaborate on how such a framing is key to support inclusivity and collaboration between diverse research perspectives, policy objectives across scales and implementation practices to deliver just and successful NbS. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.